PENDIDIKAN KETERAMPILAN BERPIKIR KRITIS DAN KREATIF SERTA KEPEKAAN SOSIAL GURU DALAM MENGAJAR - I Nyoman Sueca (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
Education Skills is expected to provide knowledge that allows people to overcome life problems in their professional duties and in daily life. Therefore teachers in carrying out their duties professionally, critical and creative thinking skills are needed, problem solving skills and decision making, as well as in Higher Education lecturers educate their students to be able to think critically and creatively in solving all problems they face. The development of critical and creative thinking skills carried out by teachers and lecturers is an educational orientation that fits in life situations that change very quickly